Exploring emerging occupational therapy identity and the development of graduate attributes among occupational therapy students - Boehm, J.; Tanner, B.; Lowrie, D.; Bonassi, M.; Brown, N.; Thomas, Y.; Cordier, Reinie (The College of Occupational Therapists - UK, 2015)
Introduction - Strong professional identity allows for appropriate representation and promotion of occupational therapy. Academic education assists in the development of occupational therapy identity. This study aims to explore the development of occupational therapy identity and graduate attributes in occupational therapy students after the first year of a revised curriculum. Method - Occupational therapy students (n = 58) were surveyed at the commencement of the second year. Data analysis used descriptive statistics and inferential statistics (χ2 for trend). Results - A total of 54 students (93.1%) completed the survey. Students progressively developed occupational therapy identity over time. There were no significant associations between main factors influencing the original decision to study occupational therapy and when occupational therapy identity developed. However, there were significant associations between main factors influencing students' decision to continue studying and when identity developed. Most students agreed the curriculum equipped them to develop graduate attributes, although this was not significantly associated with factors that either influenced students to study, or continue studying, occupational therapy. There was significant association between development of graduate attributes and occupational therapy identity over time. Conclusion - This study showed an emergence of occupational therapy identity and graduate attributes in students, demonstrating the importance of first year curriculum in the development of these factors.